2020
DOI: 10.1073/pnas.2009786117
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of β 2 AR-G s and β 2 AR-G i complex formation by NMR spectroscopy

Abstract: The β2-adrenergic receptor (β2AR) is a prototypical G protein-coupled receptor (GPCR) that preferentially couples to the stimulatory G protein Gs and stimulates cAMP formation. Functional studies have shown that the β2AR also couples to inhibitory G protein Gi, activation of which inhibits cAMP formation [R. P. Xiao, Sci. STKE 2001, re15 (2001)]. A crystal structure of the β2AR-Gs complex revealed the interaction interface of β2AR-Gs and structural changes upon complex formation [S. G. Rasmussen et al., Nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 30 publications
(60 reference statements)
3
36
0
Order By: Relevance
“…Although downstream efficacy is an important metric for drug discovery purposes, alternative methods are required to characterize the molecular basis of receptor activation. Spectroscopy experiments have proven useful for this purpose ( Gregorio et al, 2017 ; Imai et al, 2020 ; Kofuku et al, 2012 ; Manglik et al, 2015 ; Ma et al, 2020 ; Nygaard et al, 2013 ; Ueda et al, 2019 ; Weis and Kobilka, 2018 ), yet they are often difficult to compare quantitatively to atomistic simulations due to chemical modifications introduced and/or complex interpretation of measured signals. 19 F-fluorine NMR and double electron-electron resonance (DEER) spectroscopy experiments have shown that the conformational ensembles of carazolol and the apo receptor have similar TM6 distance distributions ( Manglik et al, 2015 ), in agreement with the similarity in their microswitch expectation values and free energy landscapes ( Figure 2b,f and Figure 2—figure supplement 8e ).…”
Section: Resultsmentioning
confidence: 99%
“…Although downstream efficacy is an important metric for drug discovery purposes, alternative methods are required to characterize the molecular basis of receptor activation. Spectroscopy experiments have proven useful for this purpose ( Gregorio et al, 2017 ; Imai et al, 2020 ; Kofuku et al, 2012 ; Manglik et al, 2015 ; Ma et al, 2020 ; Nygaard et al, 2013 ; Ueda et al, 2019 ; Weis and Kobilka, 2018 ), yet they are often difficult to compare quantitatively to atomistic simulations due to chemical modifications introduced and/or complex interpretation of measured signals. 19 F-fluorine NMR and double electron-electron resonance (DEER) spectroscopy experiments have shown that the conformational ensembles of carazolol and the apo receptor have similar TM6 distance distributions ( Manglik et al, 2015 ), in agreement with the similarity in their microswitch expectation values and free energy landscapes ( Figure 2b,f and Figure 2—figure supplement 8e ).…”
Section: Resultsmentioning
confidence: 99%
“…Although downstream efficacy is an important metric for drug discovery purposes, alternative methods are required to characterize the molecular basis of receptor activation. Spectroscopy experiments have proven useful for this purpose (Gregorio et al, 2017;Imai et al, 2020;Kofuku et al, 2012;Manglik et al, 2015;Ma et al, 2020;Nygaard et al, 2013;Ueda et al, 2019;Weis and Kobilka, 2018), yet they are often difficult to compare quantitatively to atomistic simulations due to chemical modifications introduced and/or complex interpretation of measured signals. 19F-fluorine NMR and double-electron resonance (DEER) spectroscopy experiments have shown that the conformational ensembles of carazolol and the apo receptor have similar TM6 distance distributions (Manglik et al, 2015), in agreement with the similarity in their microswitch expectation values and free energy landscapes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GPCRs are dynamic proteins and exist in an equilibrium among multiple conformational states even in the absence of agonist binding. The well characterized conformational states through crystallography [1][2][3]19], and electron microscopy [20][21][22] There are NMR [17,18,[24][25][26][27][28][29], DEER [30][31][32][33], FRET [34][35][36][37] and other experimental studies [38][39][40] that clearly illustrate that ligand selectively bind and stabilize specific receptor conformations [40][41][42][43] that shifts the equilibrium and the relative population of the various conformational states.…”
Section: Gpcrs Exhibit a Continuum Of Conformation Statesmentioning
confidence: 99%